A Look at the Book of Four Masters: An Excerpt for the Lesson “Iraqi Literary Poets” - Jamileh Akhyani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of writing a literary university selection should, as a rule, be to briefly acquaint students with the ideas and art of the great masters of Persian literature in order to increase their motivation to refer to the works of these masters. Book of Four Masters by Dr. Kazem Dezfoulian, published by The Organization for Researching and Composing University textbooks in the Humanities (Samt Publications) for the poetry of Iraqi Literature, is one of those excerpts whose publication, unfortunately, does not meet the expectations of the academic community. Choosing the wrong poems, misreading some verses and misinterpreting them, incorrect or incomplete explanation of some verses, not paying attention to the incorrect recording of some words and the lack of explanation about them, and a lot of typing mistakes are among the most important shortcomings mentioned above that keep the book away from the sophistication expected of a college textbook. In the present article, part of the book’s many shortcomings is discussed under the heading of “disorganized” and “inexplicit,” and the author hopes that with the attention of textbook writers, more attention will be paid to overseeing academic publishing centers and fixing these bugs in future releases.